Occurrence of Aflatoxin M1 in Milk Consumed in Tirana, Albania, and Health Risk Assessment in Different Population Groups - Andrin Tahiri; Josif Risto; Lorena Mato; Alma Cani; Dritan Topi (Toxins)
This study evaluated the prevalence of aflatoxin M1 (AFM1) in milk marketed in Tirana, Albania, along with dietary exposure and associated potential health risks. The World Health Organization has categorized Albania in cluster G02 of GEMS/FOOD, highlighting that milk is a staple in the Albanian diet, which points to a possible health risk. A total of 141 milk samples, comprising both Ultra-High Temperature (UHT) and pasteurized types, were collected from local markets in Tirana and analyzed from March 2023 to February 2024. The determination of AFM1 levels was carried out using High-Pressure Liquid Chromatography with a Fluorescence Detector (HPLC-FLD), a precise and dependable technique for identifying and measuring aflatoxins in food products. Aflatoxin M1 was found in 62.4% of the milk samples, with 26.2% surpassing the European Union’s maximum residue levels (MRL). The mean AFM1 concentrations were 58.8 ± 95.8 ng/kg, reaching a maximum level of 399.0 ng/kg. The Estimated Daily Intake (EDI) for various groups—toddlers, children, adolescents, and adults—was determined to be 2.161, 1.297, 0.519, and 0.370 ng/kg of body weight per day, respectively. The Hazard Index (HI), derived from the AFM1 exposure for four population groups, was 10.81 (toddlers), 6.48 (children), 2.59 (adolescents), and 1.85 (adults). The Margin of Exposure (MoE) was 1.85, 3.08, 7.71, and 10.81, respectively. The incidence of hepatocellular carcinoma (HCC) per 100,000 people in the four groups was 0.034, 0.021, 0.008, and 0.006, respectively. The study is the first comprehensive evaluation of AFM1 prevalence, highlighting the potential risks associated with milk consumption, as milk is a dietary staple in Albanian households. It addresses a critical public health concern regarding aflatoxin M1 (AFM1) contamination in milk consumed in Tirana, Albania, by highlighting the need for ongoing monitoring, regulatory measures, and educational outreach to enhance food safety and safeguard public health in Albania, as well as in other regions facing similar concerns.